Effectiveness of the Implementation of Nurse Communication Using the SBAR Method on the Implementation of Weighing and Acceptance in the Inpatient Room of Benyamin Guluh Hospital, Kolaka Regency - Musdalifah, Musdalifah; Risky, Sartini; Asri, Andi (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: Based on a preliminary study, it was found that there was still a lack of nurses in the implementation of SBAR communication at Benyamin Guluh Hospital, Kolaka Regency, which had started since 2016 ahead of the implementation of the first phase of National Accreditation. This study aims to analysis the influence of the SBAR method in terms of situation and background aspects on the implementation of acceptance weighing in the inpatient room at Benyamin Guluh Hospital, Kolaka Regency. Method: This study is a quantitative research with a cross sectional study approach. The population in the study amounted to 151 people with a sample of 61 respondents. Sampling using stratified random sampling. Data collection uses questionnaires and data from agencies related to the research. Data analysis using chi square test. Result: The results of the research obtained the component of the situation (X2count = 13,217 > X2table = 3,841) and background components (X2count = 9,105 > X2table = 3,841). Conclusion: There is a relationship between the components of the situation and background with the implementation of of acceptance weighing in the inpatient room at Benyamin Guluh Hospital, Kolaka Regency.